Large electrocaloric effect in tetragonal perovskite 0.03Bi(Mg1/2Ti1/2)O3–0.97(0.875Bi1/2Na1/2TiO3–0.125BaTiO3) lead-free ferroelectric ceramics. (15th March 2019) - Yan, Xiaofen; Zhu, Mankang; Wei, Qiumei; Lu, Sheng-Guo; Zheng, Mupeng; Hou, Yudong
Abstract: In this work, we reported a large electrocaloric effect (ECE) in tetragonal perovskite 0.03 Bi(Mg1/2 Ti1/2 )O3 –0.97(0.875Bi1/2 Na1/2 TiO3 –0.125BaTiO3 ) ceramic. It was found that the composition demonstrates a coexisting state of the ferroelectric P4mm and relaxor P4bm. Due to the field-induced phase transition from relaxor with P4bm symmetry to ferroelectric with P4mm symmetry, a positive ECE is observed in the temperature range of 25–130 °C. Under an electric field of 4 kV/mm, a large temperature change Δ T of 0.75 °C was achieved at 80 °C, and the EC responsivity Δ T max /Δ E of 0.19 K·cm/kV, indicating a promising lead-free material for potential application in solid-state refrigerators. Graphical abstract: Unlabelled Image